2009
DOI: 10.1590/s0074-02762009000600012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus infection and associated factors among male illicit drug users in Cuiabá, Mato Grosso, Brazil

Abstract: Intravenous drug injection has been reported as the main risk factor for hepatitis C virus (HCV) infection. The aim of the present study was to describe the prevalence and the epidemiological profile of HCV infection among abusers of illegal injected and non-injected drugs in 5%). Logistic regression analyses showed independent associations between HCV infection and intravenous drug use, imprisonment and increasing age. In the present study, inject-, imprisonment and increasing age. In the present study, injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
4
10
0
Order By: Relevance
“…This result corresponds well with that of a previous study of Korean injecting drug users [Yun et al, 2008] as well as in patients with HCV-related chronic liver disease in Korea [Suh and Jeong, 2006]. In other countries, genotype 1a [Beld et al, 1998;Muasya et al, 2008;Novais et al, 2009] or 3a [Kalinina et al, 2001;Micalessi et al, 2008;Sereno et al, 2009;Demetriou et al, 2010;Mehta et al, 2010;Ciccozzi et al, 2011] were reported as the most common genotype among injecting drug users. With regard to the treatment outcome, genotype 1 is generally associated with lower rates of the complete eradication with interferon a therapy [Scott and Gretch, 2007].…”
Section: Discussionsupporting
confidence: 90%
“…This result corresponds well with that of a previous study of Korean injecting drug users [Yun et al, 2008] as well as in patients with HCV-related chronic liver disease in Korea [Suh and Jeong, 2006]. In other countries, genotype 1a [Beld et al, 1998;Muasya et al, 2008;Novais et al, 2009] or 3a [Kalinina et al, 2001;Micalessi et al, 2008;Sereno et al, 2009;Demetriou et al, 2010;Mehta et al, 2010;Ciccozzi et al, 2011] were reported as the most common genotype among injecting drug users. With regard to the treatment outcome, genotype 1 is generally associated with lower rates of the complete eradication with interferon a therapy [Scott and Gretch, 2007].…”
Section: Discussionsupporting
confidence: 90%
“…The factors associated with HCV infection detected in illicit drug users in Breves are similar to those reported in epidemiological studies in different Brazilian municipalities for this risk group [3][4][5][6]11 . Specifi cally, the risk factors for HCV infection are identical to those detected in cocaine users in the State of Pará 11 , thus confi rming the local epidemiological profi le of HCV transmission in illicit drug users.…”
supporting
confidence: 77%
“…In Brazil, epidemiological studies of HCV infection in illicit drug users are still rare. The prevalence of HCV infection in illicit drug users sampled in metropolitan areas in the Northeast, Midwest, South and Southeast regions of Brazil ranged from 5% to 36% [3][4][5][6][7] . There are frequent reports of clinical cases of hepatitis or pathologies associated with HCV infection in other population groups in northern Brazil [8][9][10][11] .…”
mentioning
confidence: 99%
“…This may also indicate that longer exposure to risk factors increases the probability of infection with HCV. These two risk factors for HCV infection have also been detected in other Brazilian populations, including blood donors in the Brazilian state of Pará [12,15,17,33]. …”
Section: Discussionmentioning
confidence: 87%